CDK4/6 inhibitor resistance in estrogen receptor positive breast cancer, a 2023 perspective - Zhou, Fiona H.; Downton, Teesha; Freelander, Allegra; Hurwitz, Joshua; Caldon, C. Elizabeth; Lim, Elgene (Frontiers in Cell and Developmental Biology, 2023)
CDK4/6 inhibitors have become game-changers in the treatment of estrogen receptor-positive (ER+) breast cancer, and in combination with endocrine therapy are the standard of care first-line treatment for ER+/HER2-negative advanced breast cancer. Although CDK4/6 inhibitors prolong survival for these patients, resistance is inevitable and there is currently no clear standard next-line treatment. There is an urgent unmet need to dissect the mechanisms which drive intrinsic and acquired resistance to CDK4/6 inhibitors and endocrine therapy to guide the subsequent therapeutic decisions. We will review the insights gained from preclinical studies and clinical cohorts into the diverse mechanisms of CDK4/6 inhibitor action and resistance, and highlight potential therapeutic strategies in the context of CDK4/6 inhibitor resistance.